2022
DOI: 10.2166/wh.2022.094
|View full text |Cite
|
Sign up to set email alerts
|

Modeling infection from SARS-CoV-2 wastewater concentrations: promise, limitations, and future directions

Abstract: Estimating total infection levels, including unreported and asymptomatic infections, is important for understanding community disease transmission. Wastewater can provide a pooled community sample to estimate total infections that is independent of case reporting biases toward individuals with moderate to severe symptoms and by test-seeking behavior and access. We derive three mechanistic models for estimating community infection levels from wastewater measurements based on a description of the processes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…Conversely, IBV and RSV A concentrations were lowest suggesting limited circulation of those viruses. Future work is needed to document time varying patterns of respiratory viral RNA inputs from infected individuals to the wastewater system to enable modeling of the number of infected individuals in a sewershed from wastewater viral RNA concentrations 27 and to enable modeling of epidemiological parameters like the reproductive number from wastewater data 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, IBV and RSV A concentrations were lowest suggesting limited circulation of those viruses. Future work is needed to document time varying patterns of respiratory viral RNA inputs from infected individuals to the wastewater system to enable modeling of the number of infected individuals in a sewershed from wastewater viral RNA concentrations 27 and to enable modeling of epidemiological parameters like the reproductive number from wastewater data 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Where that information is available, ELISA optical density or titer measurements may be extrapolated to a bulk copies per person measurement, in a way that is analogous to the handling of viral copy number data. 29 Because the protocol is able to detect antibodies in frozen archived wastewater samples, it becomes possible to analyze the SARS-CoV-2 pandemic retrospectively and to develop such models while simultaneously testing their predictive value against historic incidence levels. Leveraging existing samples collected throughout the COVID-19 pandemic to conduct historic longitudinal studies that simultaneously quantify concentrations of antibodies and integrate that information with viral load and case data for the corresponding sewershed population.…”
Section: Discussionmentioning
confidence: 99%
“…15-17 It has also been shown that WBE of SARS-CoV-2 has a strong correlation with clinically diagnosed case numbers; 12 further, the WBE methodology is not dependent on external factors (e.g., testing and reporting rates, reporting lag, and reporting biases). 12,18,19…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] It has also been shown that WBE of SARS-CoV-2 has a strong correlation with clinically diagnosed case numbers; 12 further, the WBE methodology is not dependent on external factors (e.g., testing and reporting rates, reporting lag, and reporting biases). 12,18,19 In this study, we captured and enriched SARS-CoV-2 in the wastewater, reported sitespecific sequencing and variant analysis, and described the implications of these data. Further, we performed a respiratory viral pathogens (RVP) panel analysis for other respiratory diseasecausing viruses in these samples.…”
Section: Introductionmentioning
confidence: 99%